FREE VIBRATION ANALYSIS OF NOTCHED COMPOSITE LAMINATED CANTILEVER BEAMS (Journal of Engineering, 2011)
The present work divided into two parts, first the experimental side which included themeasuring of the first natural frequency for the notched and unnotched cantilever composite beamswhich consisted of four symmetrical layers and made of Kevlar- epoxy reinforced. A numericalstudy covers the effect of notches on the natural frequencies of the same specimen used in theexperimental part. The mathematical model for the beam contains two open edges on the uppersurface. The effect of the location of cracks relative to the restricted end, depth of cracks, volumefraction of fibers and orientation of the fiber on the natural frequencies are explored. The resultswere calculated using the known engineering program (ANSYS), the results obtained has beencompared with those calculated analytically by (Sierakowski RL.), which have expressed the closestwell also the comparison between the experimental results with that calculated by (ANSYS) hasvery well. The study shows that the highest difference in frequencies occur when the value of thefiber orientation equal to 0odegree, the effect of location of the cracks decrease when the cracksmoving toward the free end and also shows that an increase of the depth of the cracks leads to adecrease in the values of natural frequencies.